2015
DOI: 10.1159/000437247
|View full text |Cite
|
Sign up to set email alerts
|

Early Upregulation of NLRP3 in the Brain of Neonatal Mice Exposed to Hypoxia-Ischemia: No Early Neuroprotective Effects of NLRP3 Deficiency

Abstract: Background: The NLRP3 inflammasome acts as an early mediator of inflammation by cleaving and releasing IL-1β and IL-18 from their proforms. Objective: The aim of this study was to describe NLRP3 activation and evaluate whether deficiency of NLRP3 protects against neonatal hypoxic ischemic brain damage. Methods: C57BL/6 and NLRP3-/- mice at P9 were subjected to unilateral common carotid ligation followed by hypoxia. RT-PCR was used on mRNA in five different subregions of the brain. Brain infarction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
2
28
1
Order By: Relevance
“…We previously reported that NLRP3 is upregulated after neonatal hypoxia-ischemia and that early expression is seen in astrocytes (3 h), while microglial expression of NLRP3 is evident after 24–72 h [6]. However, we did not find any difference in early infarction volume (24 h) between NLRP3-deficient mice and wild-type (Wt) mice after hypoxia-ischemia.…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We previously reported that NLRP3 is upregulated after neonatal hypoxia-ischemia and that early expression is seen in astrocytes (3 h), while microglial expression of NLRP3 is evident after 24–72 h [6]. However, we did not find any difference in early infarction volume (24 h) between NLRP3-deficient mice and wild-type (Wt) mice after hypoxia-ischemia.…”
Section: Introductioncontrasting
confidence: 70%
“…Circulating levels of IL-1β, IL-18, and tumor necrosis factor (TNF) were measured in plasma as previously described [6], using Meso Scale technology (MesoScale, Diagnostics) and Bio-Plex suspension array (Bio-Rad Laboratories Inc.) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Nlrp3 RNA expression and protein levels were also increased in the brain following hypoxia-ischemia (HI) in a mouse model [22]. At earlier time points following HI, NLRP3 expression was detected in astrocytes in the hippocampus and the thalamus, and at later time points both astrocytes and microglia showed increased NLRP3 expression [22] .…”
Section: Hypoxia Priming Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…Nlrp3 RNA expression and protein levels were also increased in the brain following hypoxia-ischemia (HI) in a mouse model [22]. At earlier time points following HI, NLRP3 expression was detected in astrocytes in the hippocampus and the thalamus, and at later time points both astrocytes and microglia showed increased NLRP3 expression [22] . Furthermore, hypoxic exposure was found to increase the levels of NLRP3, AIM2, and pro-IL-1 in human prostate epithelial cells, in prostate cancer cell lines, and in THP-1 cells, and was targeted using an NF-κB inhibitor [23] .…”
Section: Hypoxia Priming Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…In particular, the secretion of IL‐1β and IL‐18 requires the NOD (nucleotide‐binding oligomerization domain)‐like receptor (NLR) Pyrin domain containing 3 (NLRP3) inflammasome (Singh and Jha, 2018; Song et al, 2017). NLRP3 activation has been reported to mediate injury in various CNS disorders including HIE (Ystgaard et al, 2015; Chen et al, 2018). The up‐regulation of NLRP3 was found in several regions of the brain at 24 h after neonatal HI (Ystgaard et al, 2015; Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%